Design and construction of an automated monitoring system for mobile network system error with control chart - Noppakit Konjai (2018)
An objective of this research is to design and construct an automated monitoring system for mobile network system error with control chart. The two stage control chart has been used to monitor the cancelled or terminated calls resulting from an error of base station system belonging to Advance Info Service Public Company Limited in the north region of Thailand in order to rapidly solve a problem and increasing the quality of service. By gathering information, it was found that an error of base station system led to call cancellations and call terminations (TCH Drop) are about 0.72% which was used to design the control limit of the Two Stages Cumulative Count Control Chart that was appropriate for monitoring a process that low errors occur, this project set the probability of the type one error (α) equal 0.05. Furthermore, in accordance with the control chart, we divided this error type into two parts using equal to 0.14. The calculation indicates that, the first control limit (n1) was 6 and the second control limit n2 was 24. We tested these two parameters by simulating the usage of TCH per hour which was based on Poisson distribution and the past information of 0.72% TCH Drop was based on Binomial distribution and the usage of TCH per hour. The results from the simulation showed that the increasing of n1 and n2 to be 9 and 30 respectively are necessary in order to meet the design requirement. This chart was also applied to the network and it can monitor the network effectively. This research can monitor any error of the network and send an alarm to solve the problem immediately to guarantee the best service to customers.